Evaluation of Demonstrations on Rapeseed in district Ferozepur of Punjab - Gill, Jagjot Singh (Indian Journal of Extension Education, 2024)
Punjab Agricultural University Farm Advisory Service Centre, Ferozepur conducted demonstrations on rapeseed (gobhi sarson variety GSC 7) on farmer’s fields in district Ferozepur during rabi seasons (October to March) during the years 2019-20, 2020-21, 2021-22 and 2022-23 in 20.71 ha area, respectively. Punjab Agricultural University recommended variety GSC 7 of gobhi sarson with improved agricultural practices in demonstration plots produced significantly higher grain yields of 22.4, 22.2, 20.1, and 21.3 q ha-1 as compared to 17.2, 14.8, 15.6, and 17.8 q ha-1 in check plots during rabi 2019-20, 2020-21, 2021-22 and 2022-23, respectively. Demonstration plots recorded an average increase in yield of 24.5 percent over check plots. The average extension gap, technology gap, and technology index were 5.2 q ha-1, 3.5 q ha-1, and 14.0 percent, respectively. A higher average net return of Rs. 73511.3 ha-1 was obtained in demonstration plots, which was 30.9 percent greater than check plots with a net return of Rs. 50768.8 ha-1.